Language and Identity in Indian Diasporic Literature - Singh, Ravindra Kumar (Integrated Journal for Research in Arts and Humanities, 2024)
The complex relationship between language, culture, and identity has long been a central concern in the study of diasporic literature, particularly in the context of the Indian diaspora. This paper explores how the poetics of cultural transrelation in Indian diasporic writing challenges the notion of a fixed, monolithic identity, and instead embraces the fluidity and multiplicity inherent in the diasporic experience.